Home > NFA TO DFA C Program

Conversion Of E-NFA To DFA

Conversion Of E-NFA To DFA Let M=(Q,Σ,δ,q0,F) Be The NFA M1=(Q1,Σ,δ1,q01,F1) Be The Equivalent DFA   1) Initial State:-  q01 - ε-Closure(q0) 2) Construction Of δ1 δ1(q,x)=ε-Closure(δ(q,x)) Start The Construction Of δ1 With Initial State And Continue For Every New State. 3) Final State:- Every Subset Which Contain The Final State Of ε-NFA Is Final State Of DFA   Example:- 1)  Initial State:- q01=ε-Closure(q0) ={q0,q1} q0=q0,q1 2) DFA  

Read More

NFA With ε-Moves Or ε-NFA

NFA With ε-Moves Or ε-NFA The NFA Which Has Transition Even For Empty String ε Is The Called An ε-nfa ε-NFA Has 5-Tuple M=(Q,Σ,δ,q0,F) Where Q=Set Of States Σ=I/p Alphabets δ=Transition Function(Q×Σ∪{ε}--> 2Q) q0=Initial State F= Final State Q×Σ--> Q--> DFA Q×Σ--> 2Q-->NFA Q×Σ∪{ε}--> 2Q--> ε-NFA   Example L={am,bm/m,n≥0} L={a,b,ε,ab,abb...} 2.L={anbUbna/n≥0} 3.L={(ab)n/n≥0}

Read More

NFA Example: Consider The NFA M Given Below

Consider The NFA M Given Below Let 'M' Be The NFA Obtain From M By Converting All The Non-Final States Into Final States If L & L1 Be The Language Accepted  By M And M1 Then Which Of The Following Statement Is Correct. a) L=L1 b) L⊂L1 c) L1⊂L d) L∩L1=Φ e) L∪L1=Σ* f) None   Before Solving This Problem I'll Tell Yo

Read More

NFA Problem

NFA Problem - Consider The NFA M Given Below. Let 'M' Be The NFA Obtain From By Interchanging Final And Non- Final States. Let L And L1 Be The Language Accepted By M And M1 Respectively Then Which Of The Following Statement Is True. L=L1 L⊆L1 L1⊆L L∩L1=Φ L∩L1=Σ* L∪L1=Φ L∪L1=Σ* Solution:- Given NFA 'M' Is He

Read More

Conversion Of NFA To DFA

Conversion Of NFA To DFA Construct The DFA For The Following NFA Solution:- DFA TRANSITION TABLE AFTER MERGING SAME STATES TO ONE STATE, I'LL DELETE ONE OF THESE STATES If You Observe Given NFA The String Is Containing ab As Substring. In This D FA Also The String Contains ab As Substring.   Every State In This Given

Read More

Conversion Of NFA To DFA

Conversion Of NFA To DFA Construct The DFA For The Following NFA Solution:- I Want You To See Previous Problem Before Solving This Problem Because You'll Understand Easily If You See Previous Problems. Conversion Of NFA To DFA   STEPS Step 1 - Initial State Will Be Same In DFA Transition Table i.e. q0 Step 2 - 'q0's 0

Read More

NFA To DFA Conversion

NFA To DFA Conversion NFA Is Not Real Machine. But Where We Use This Machine? When We Get A Complex Problem. Creating NFA For That Problem Becomes Easy For Solving Problem.   For Complex Problem We Create NFA First And Then We Will Convert It To DFA To Solve Complex Problems.   Creating Directly DFA For A Problem

Read More